Sabotage in dynamic tournaments; Sabotage in dynamischen Turnieren - Oliver Gürtler; Johannes Münster (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
This paper studies sabotage in a dynamic tournament. Three players compete in two rounds. In the final round, a player who is leading in the race, but not yet beyond the reach of his competitors, gets sabotaged more heavily. As a consequence, if players are at the same position initially, they do not work productively or sabotage at all in the first round. Thus sabotage is not only directly destructive, but also depresses incentives to work productively. If players are heterogeneous ex ante, sabotage activities in the first round may be concentrated against an underdog, contrary to findings from static tournaments. We also discuss the robustness of our results in a less stylized environment. – – Dieser Aufsatz untersucht Sabotage in einem dynamischen Turnier. Drei Spieler konkurrieren in zwei Runden. In der letzten Runde wird ein Spieler, der einen Vorsprung hat, aber noch einholbar ist, stärker sabotiert. Deshalb wird eine Gruppe mit homogenen Spielern in der ersten Runde weder produktiv arbeiten noch sabotieren. Sabotage ist also nicht nur direkt destruktiv, sondern verringert auch die Anreize zu produktiver Anstrengung. Wenn die Spielergruppe ex-ante heterogen ist, kann sich Sabotage in der ersten Runde überwiegend gegen schwächere Spieler richten, im Gegensatz zu Ergebnissen aus statischen Turnieren. Unsere Ergebnisse bleiben auch in einem weniger eng definierten Modellrahmen robust bestehen.
Keywords: 330; Dynamic tournaments; contests; sabotage; heterogeneity